Simulation Approach to Biodiesel Production from Palm Oil by Conventional and Reactive Distillation Processes - Kottititum, Bundit; Chakton , Kantarod; Srinophakun, Thongchai Rohitatisha (Agriculture and Natural Resources, 2014)
A simulation and design method was proposed for biodiesel production from palm oil. The reactant contained three main fatty acids: palmitic, oleic and linoleic acids. The molecular structure design enabled all parameters to be estimated for the process model and simulation. The biodiesel production simulated both conventional and reactive distillation processes. The purity from the conventional process, catalyzed by sodium hydroxide (homogeneous) and strontium oxide (heterogeneous) was 99.45 and 95.21%, respectively. On the other hand, the purity from reactive distillation with strontium oxide (99.87%) was higher than with sodium hydroxide (99.52%). The steady state result was used for the economic simulation of the equipment design. The total cost of biodiesel production using sodium hydroxide and strontium oxide catalysts in a conventional distillation process was USD 0.6701 L-1 and USD 0.6291 L-1, while for the reactive distillation process, the total cost was USD 0.6302 L-1 and USD 0.6262 L-1, respectively.